THE MODERATOR ROLE OF TRUST IN THE RELATIONSHIP BETWEEN COOPETITION AND INCREMENTAL INNOVATION: EVIDENCE FROM TOURISM INDUSTRY - Fatma YAVUZ; Murat ÇEMBERCI (Geo Journal of Tourism and Geosites, 2022)
With the increasing importance of coopetition in recent days, coopetition has been adopted by companies in order to embark on the changing global market conditions. Cooperation is a variable that arises simultaneously from the concepts of “cooperation” and “competition” that has become increasingly popular in recent years. In cooperation, the attitude of the partners is important. During the competition process, the attitudes and behaviors of the partners towards each other should be within the framework of ethical and moral rules, competence, efficiency and goodwill. It is believed that the efficiency of the innovation process, which takes place together with the coopetition path, will be greater. It is aimed to improve the innovation performance of companies through strong cooperation between companies and synergy in the information of the parties. The element of trust is one of the important factors determining the direction of coopetition activities particular. For this, the trust factor between partners often comes into play. This research questions how innovative firms that conduct R&D and innovation studies affect trust in the relationship between coopetition efforts and incremental innovations in tourism industry. For this reason, it is aimed to examine the moderator effect of trust in the relationship between cooperation and incremental innovation. The analysis of the data collected in the study was tested by hierarchical regression analysis. The positive and significant impact of joint competitive activities on the hospitality industry was further strengthened by the moderator effect of the trust and supported by the results of the resulting field study. As a result, the study was finalized by supporting the assumption put forward.